AR_GERICHTE OG O5V-14-23 vom 11. März 2015 - AR Gerichte (2015)
Obergericht Appenzell Ausserrhoden 5. Abteilung Urteil vom 11. März 2015 Mitwirkende Obergerichtspräsident E. Zingg Oberrichter R. Krapf, S. Plachel, Dr. M. Winiger, E. Graf Obergerichtsschreiber J. Kürsteiner Verfahren Nr. O5V 14 23 S